Fatal podophyllin poisoning with multi-organ toxicity: A case report - Bhakti U Sarangi; Shridhar Jadhav; Ajay Walimbe; Manikiran Reddy; Siddhi Gawhale; R Hema Priya (Wolters Kluwer Medknow Publications, 2023)
Accidental poisoning with household products is one of the leading causes of involuntary injuries among children in low- and middle-income countries. Podophyllin poisoning is a rare and potentially fatal occurrence. The podophyllotoxin is a lipid-soluble cytotoxic compound with no antidote and its toxicity includes life-threatening neurological and multisystem complications. We report a case of a 2-year-old girl with accidental podophyllin poisoning causing multi-organ dysfunction who did not survive despite timely aggressive support and explore the possibility of early use of activated charcoal and role of extra-corporeal therapies such as hemoperfusion as a life-saving measure in such situations.